Study of Passenger Perceptions for Public Transport During Covid 19 in Pekanbaru, Indonesia - Muttaqin, Muchammad Zaenal; Irfan Ramanda; Cyintia Kumala Sari (Rumah Jurnal, 2023)
During the COVID-19 pandemic, the manager of the Trans Metro Pekanbaru bus limited the number of passengers, operating hours, and rit. This policy follows the implementation of a transition period to the new normal in Pekanbaru City. With the enactment of this government policy, it has made an impact on the performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic. This study analyzes the performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic based on passenger operations and perceptions. The research methods used in this study are quantitative and qualitative. The data analysis used is the analysis of operational performance data during the COVID-19 period, and the analysis of passenger perceptions of service performance during the COVID-19 period. The results of this study show that the operational performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic based on load factor, headway, and frequency indicators is considered poor. The average load factor value on all routes is below 70%, with the highest and lowest average values being 42% on the Ramayan – Pandau route and 2% on the Unilak – Palas Raya route. The average headway value on all routes is more than 10 minutes, with the highest average score being 63 minutes on the BRPS - UIN and Ramayana - Unilak routes. The average frequency value on all routes is only 1-3 vehicles/hour on average, with the highest average value being 5 vehicles/hour on the Ramayana - Pandau route. Based on passenger perceptions, it shows that passengers' perceptions of the quality of Trans Metro Pekanbaru public transportation services during the COVID-19 pandemic are considered good. This can be seen from the average score of respondents' assessment of 74.86%.